Islamisasi Ilmu Pengetahuan: Sosiologi Islam sebagai Sebuah Tawaran - Rahardjo, Mudjia (UIN Maulana Malik Ibrahim Malang, 2002)
A discourse on the Islamization of science has grown among Muslim scholars since the last three decades. It begins with the view that Western science is no longer able to understand non-Western cultural systems, including Islamic culture. Inevitably this issue then becomes one of the most interesting academic discourse and invites public debate in various circles, especially Muslim intellectuals. This paper presents discourses on the issues that occur and then tries to look for possibilities in the future, especially in the field of sociology. Three sociological theories analyzed in this paper are structural-functional theory, conflict theory and the theory of symbolic interactionism which are compared to Islamic views. There are two things that distinguish between Islamic and contemporary sociology concerning the general treatment of religion and the application of sociology. Realizing the concept or theory of Islamic sociology will be a great job for Muslim sociologists because some existing grand theories can contain a perspective bias that is inconsistent with Islamic values and teachings. Sejak tiga dekade terakhir tumbuh di kalangan ilmuwan Muslim sebuah diskursus tentang Islamisasi ilmu, pengetahuan yang berawal dari pandangan bahwa ilmu Barat tidak lagi mampu memahami sistem kebudayaan non- Barat, termasuk kebudayaan Islam. Tak pelak persoalan ini lantas menjadi salah satu wacana akademik paling menarik dan mengundang debat publik di berbagai kalangan, khususnya intelektual Muslim. Tulisan ini memaparkan diskursus seputar persoalan yang terjadi dan kemudian mencoba mencari kemungkinannya di masa depan khususnya dalam bidang sosiologi. Tiga teori sosiologi dianalisa dalam makalah ini yaitu teori struktural-fungsional, teori konflik dan teori interaksionisme simbolik yang dibandingkan dengan pandangan Islam. Terdapat dua hal yang membedakan sosiologi Islam dan kontemporer yaitu menyangkut perlakuan umum atas agama dan penerapan sosiologi. Mewujudkan konsep atau teori sosiologi Islam akan menjadi pekerjaan besar bagi para sosiolog Muslim sebab beberapa teori inti yang ada dapat mengandung bias perpektif yang tidak sesuai dengan nilai-nilai dan ajaran Islam.